Symbolika miasta labiryntu w powieściach Marka Krajewskiego i Zygmunta Miłoszewskiego = The city-labyrinth symbolism in the novels of Marek Krajewski and Zygmunt Miłoszewski - Berdys, Marlena (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The topic of this article is the symbolism of the labyrinth which appears in Marek Krajewski`s and Zygmunt Miłoszowski`s novels. Along with the growing popularity of crime novels, there has been an increase of theoretical approaches to the genre. Contemporary practitioners of this particular genre diversify it by adding new elements. In the case of the authors who are discussed in this article, the city or town is foregrounded and depicted as a character.
Keywords: powieść kryminalna; literatura polska; miasto; symbol; 21 w.